Modern Trends in Political Economy: Analysis of Discourse and Policy Narrative of Economic Reform in Libya (2003-2010), Lessons for Future - بعيرة , أنس (Dirasat in Economics and Business, 2020)
This study tackles a new trend of political economy analysis by interjecting new theoretical and analytical frameworks of policy discourse and narrative. The aim of this research provides some insight into real dynamics behind the declared economic reform project in Libya during the period 2003-2010. The major three research questions of the study focus on: Firstly, the deficiency of the international financial institutionsIFI in attempting to interpret the process of economic change in Libya during the study period. Secondly, looking into the influence of formal and informal actors within the Libyan instituteonal context. Thirdly, trying to develop a future model for the requirement needed to implement the recommended finding to create stable Libyan economic identity. A shortcoming of the quantitative work was to ignore the effect created by the local political, social environment settings. This study used case-study method supported by both 'Discursive Institutionalism-DI' and the ‘Narrative Policy Framework-NPF' through Nvivo software. A major finding of the study is the need to introduce specific changes on policy formulation to establish s stable and clear institutional identity in Libya.